Surfactant replacement in preterm infants with respiratory distress syndrome - Dani, C. (Acta Biomedica Atenei Parmensis, 2012)
Surfactant treatment has been demonstrated to decrease pneumothorax and mortality in preterm infants (with RDS). In many neonatal intensive care units NCPAP is used immediately after birth, while surfactant is given as early rescue in infants who develop RDS. This approach has been found safe and effective in several studies and a recent meta-analysis demonstrated a decreased risk of bronchopulmonary dysplasia or death in infants following this strategy.